Garrison hospital «York» Königsberg: history of creation and further development of the infectious hospital of Kaliningrad - L. A. Perminova; J. L. Malakhova; I. B. Ivanov; O. G. Krasnova; A. D. Ebert; I. G. Skobei; A. V. Tarasov (Журнал инфектологии, 2023)
The article presents the results of the study and analysis of archival documents, on the basis of which the history of the construction of the complex of buildings of the garrison infirmary «York» in Königsberg is recreated, the features of the architectural and planning solutions used in the construction of this medical complex are studied and analyzed. The description of the post-war and modern stages of development of the infectious diseases hospital of the Kaliningrad region, which is located in the preserved buildings of the garrison infirmary «York» in Konigsberg, is given.